The Entrepreneurial Orientation Towards Msme's Performance: Role Of Resource Dimensions - Muthia Pramesti (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
In this research, the effect of entrepreneurial orientation sub-dimensions on firm performance was discussed. Previous studies had shown that Indonesian MSMEs had problems with resources especially access to finance and managerial skills. This study included the availability of financial resources and flexibility of resources as moderating variables. The study used 149 micro-enterprise owners in the "Tangan Di Atas" (TDA) Community in Indonesia. SEM-PLS on SmartPLS was used as a tool in data analysis. The findings showed that two sub-dimensions, innovativeness, and proactiveness, had a significant positive relationship with firm performance, while resource flexibility moderated the relationship of innovativeness to performance significantly. The risk-taking variable showed a positive relationship with firm performance in the moderation of financial resources.